Renal outcomes in mixed proliferative and membranous lupus nephritis (Class III/IV + V): A long-term observational study. Issue 6 (1st November 2016) - Ikeuchi, Hidekazu; Hiromura, Keiju; Kayakabe, Ken; Tshilela, Kadiombo Anastasie; Uchiyama, Kazuhiko; Hamatani, Hiroko; Sakairi, Toru; Kaneko, Yoriaki; Maeshima, Akito; Nojima, Yoshihisa
Abstract: Objectives : In this study, we aimed to assess the effect of combination of proliferative and membranous lesions (Class III + V or IV + V) on renal outcomes as an independent category distinct from Class III and IV. Methods : We retrospectively analyzed 103 Japanese patients (14 male and 89 female) with Class III/IV LN, with or without Class V, who underwent renal biopsy and were treated at our institution. Renal endpoint was defined as doubling of serum creatinine or end-stage renal disease (ESRD). Results : The number of patients in each group was as follows: pure Class III/IV, 81 patients and mixed Class III/IV + V, 22 patients. During a median follow-up period of 125.0 months, 10 patients developed renal endpoint: five had Class III/IV LN and five had a combination of Class III/IV + V. Kaplan–Meier analyses demonstrated that patients with mixed Class III/IV + V LN had significantly poorer renal outcomes than patients with Class III/IV LN. Multivariate Cox regression analyses identified serum creatinine, active and chronic lesions (A/C), and mixed Class III/IV + V) as independent risk factors for poor renal outcomes. Conclusions : This study demonstrated a combination of proliferative and membranous LN (ISN/RPS Class III/IV + V) predicts poor renal outcomes.